1997
DOI: 10.1029/97gl00093
|View full text |Cite
|
Sign up to set email alerts
|

Reactive uptake and hydration experiments on amorphous carbon treated with NO2, SO2, O3, HNO3, and H2SO4

Abstract: The reactivity and hydration properties of amorphous carbon were studied in a low-pressure Knudsen cell reactor at room temperature (298 K). Reactions of NO 2 (y = 0.11 + 0.04) and HNO 3 (y = 0.038 + 0.008) were observed and may be important for nitrogen partitioning in the atmosphere. Water uptake was measured before and after exposure to various gases. Treating the amorphous carbon with NO 2 and 03 does not alter the H20 uptake, while treatment with SO 2, HNO3, and H2SO 4 significantly increases the H20 upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
165
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(172 citation statements)
references
References 24 publications
(20 reference statements)
6
165
1
Order By: Relevance
“…With the strong seasonal variation. As indicated in Figure 18, in December, heterogeneous uptake of CH20 into sulfate aerosols, the HO x the rate of heterogeneous reaction of CH20 decreases due to the Northern Hemisphere during winter, producing a 90% decrease in [1995] and Rogaski et al [1997] have shown that the uptake CH20 and a 10% decrease in HO 2 in northern middle and high coefficient for ozone on black carbon particles occurs with an latitudes (see Figure 19). With a lower uptake coefficient for uptake coefficient of the order of 2x10 -4 to 3.3x10 -3.…”
Section: Reaction Of Ho2 On Sulfate Aerosolsmentioning
confidence: 99%
“…With the strong seasonal variation. As indicated in Figure 18, in December, heterogeneous uptake of CH20 into sulfate aerosols, the HO x the rate of heterogeneous reaction of CH20 decreases due to the Northern Hemisphere during winter, producing a 90% decrease in [1995] and Rogaski et al [1997] have shown that the uptake CH20 and a 10% decrease in HO 2 in northern middle and high coefficient for ozone on black carbon particles occurs with an latitudes (see Figure 19). With a lower uptake coefficient for uptake coefficient of the order of 2x10 -4 to 3.3x10 -3.…”
Section: Reaction Of Ho2 On Sulfate Aerosolsmentioning
confidence: 99%
“…The temporal evolution of the gas-phase O 3 concentration is shown for a base scenario with no heterogeneous chemistry and for the constant uptake scenarios A const , B const , C const . Scenarios A const , B const , C const use constant uptake coefficients of γ O 3 =1×10 −3 (Stephens et al, 1986;Pöschl et al, 2001), γ NO 2 =0.14 (Gerecke et al, 1998;Ammann and Pöschl, 2007), and γ H 2 O =0.4×10 −3 (Rogaski et al, 1997;Pöschl et al, 2001) but are otherwise equivalent to scenarios A, B, and C as defined in Table 1. surfaces that are older than six hours is not significant. After one hour of simulation time, the uptake coefficients fall by one to two orders of magnitude, depending on the scenario.…”
Section: Feedback On the Gas-phase O 3 Concentration With Differing Umentioning
confidence: 99%
“…To study the gas-phase feedback from a heterogeneous modeling approach employing constant uptake coefficients, we implement the experimentally determined constant uptake coefficients of γ O 3 =1×10 −3 for O 3 uptake , γ NO 2 =0.14 for NO 2 uptake (Gerecke et al, 1998), and γ H 2 O =0.4×10 −3 for the uptake of water vapor (Rogaski et al, 1997) into the non-emission scenarios A, B, and C. These γ X i -values represent initial uptake coefficients that were previously implemented in our model as accommodation coefficients. The gas-phase loss is computed according to Eq.…”
Section: Gas-phase O 3 Feedback For Constant Uptake Parameterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies where mainly done in Knudsen cells or in aerosol flow reactors and resulted in sometimes very high uptake coefficients of e.g. NO 2 of the order of 10 −2 on soot surfaces (Rogaski et al, 1997;Gerecke et al, 1998). Other studies found uptake rates that were several orders of magnitude lower (Kalberer et al, 1996;Ammann et al, 1998;Longfellow et al, 1999;Al-Abadleh and Grassian, 2000;Kirchner et al, 2000), surface saturation effects that result in a time dependence of the uptake (Ammann et al, 1998;Longfellow et al, 1999;Al-Abadleh and Grassian, 2000;Kirchner et al, 2000) and also a strong dependency on the type of soot used (Kalberer et al, 1996;Kirchner et al, 2000).…”
Section: Chemistry In the Plumementioning
confidence: 99%